1984
DOI: 10.1002/tcm.1770040405
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mouse embryo limb bud cell culture system for the estimation of chemical teratogenic potential

Abstract: High-density cultures of mouse embryo limb bud cells differentiate and synthesize an extracellular matrix containing sulfated proteoglycans. Since these in vitro events are related to those that occur during fetal development, we have investigated the use of cultured limb bud cells for the analysis of the activities of chemical teratogens. We have established the conditions for the use of the radiochemicals 35SO=4 and 3H-thymidine for the assessment of chemical effects on sulfated proteoglycan and DNA synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…High density cultures of mouse or chick limb bud cells have been proposed as teratogenicity screening systems by Wilk et al (1980); Hassell and Horigan (1982) and Guntakatta et al (1984). Flint and Orton (1984) and Kistler (1985) used cells from rat limb buds and Renault et al (1993) modified the system to be used with rabbit limb bud cells.…”
Section: Limb Bud Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…High density cultures of mouse or chick limb bud cells have been proposed as teratogenicity screening systems by Wilk et al (1980); Hassell and Horigan (1982) and Guntakatta et al (1984). Flint and Orton (1984) and Kistler (1985) used cells from rat limb buds and Renault et al (1993) modified the system to be used with rabbit limb bud cells.…”
Section: Limb Bud Cell Culturementioning
confidence: 99%
“…The cells proliferate and undergo differentiation into chondrocytes after 5 to 6 days in culture. The rate of proliferation and differentiation into cartilaginous nodules can easily be measured quantitatively by simple staining methods with subsequent spectrophotometry and fully automated image analysis (Renault et al 1989) or by radiochemistry (Guntakatta et al 1984). The test compound is added to the cultures in different concentrations.…”
Section: Limb Bud Cell Culturementioning
confidence: 99%
“…The maximum concentration, having no inhibitory effect for chloramphenicol, was 60 µg/mL. Chloramphenicol caused a statistically significant reduction in 35 SO 4 2-incorporation when tested in the mouse limb bud cell spot culture assay (Guntakatta et al, 1984).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Controls are treated in the same manner as experimental compounds. After the test agent has been added, the cultures are placed in 25°C incubators and are scored for cell and tissue differentiation 24 hr later. During this period, several types of cells differentiate from their stem cells, as observed by phase contrast microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Trosko and co-workers (7) found that a variety of chemicals have the ability to increase the recovery of mutant 6-TGr cells when co-cultured with wild-type 6 24 hr, at which time the medium is replaced with or without the test compound. The HEPM cells are then maintained in culture for an additional 72 hr.…”
Section: Critical Reviewmentioning
confidence: 99%